Geographic Information System for Mapping the Spread of COVID-19 in the city of Salatiga - Joshua Rondonuwu; Kristoko Dwi Hartomo; Hanna Prillysca Chernovita (Politeknik Negeri Batam, 2020)
The city of Salatiga, located in the province of Central Java, is one of the cities affected by the spread of COVID-19 in Indonesia. The first COVID-19 case in the city of Salatiga was confirmed on 31 March 2020 until now it has reached more than eighty people. The increasing number of cases and the lack of information on the spread of COVID-19 and the information provided are static. This information, this research aims to build and utilize the WebGIS application as one of the information for the spread of COVID-19 in Salatiga. Mapping the area in this application uses a shapefile file and is converted to a GeoJSON file. It uses Blogspot as web hosting and javascript leaflets to display GIS maps and designs and uses the Exponential Smoothing method to forecast COVID-19 cases and use the web equal 4.0 method for website testing. The results of this study to provide information about the spread of COVID-19 in the city of Salatiga. Interactive map and forecasts of COVID-19 cases in the city of Salatiga. In this study, the single exponential smoothing has the smallest MAPE value, namely 35.2360. It results in a prediction on July 20 to 26, 2020, which has decreased to 1 positive case consisting of the lowest number in this forecasting is -2. The highest number shows four positive cases. And the website testing using the webqual 4.0 standard, respondents agreed with the website's usability and information quality, and it was sufficient for website service interaction.